Theoretical Study of Isospin Mixing States with T> 0 in sd Even-Even N=Z Nuclei Using Shell Model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nuclear excited states with T > 0 in sd even-even N=Z  nuclei have been studied by using shell model. The calculations have employed the USDB Hamiltonian in order to predict the energy levels, the reduced electric quadrupole transition probabilities and reduced magnetic dipole transition probabilities. The study also include the average number of nucleons in each sd- active orbitals. The results compared with available experimental data.  The comparison showed a good agreement between theoretical and experimental energy sates for most of the states studied in this work. On the other hand there was a difference between theoretical and experimental values of transition probabilities, but it can be said that it remained within the acceptable range of the difference.